Phytoremediation of nickel by Paraserianthes falcataria with varying levels of manure - Hilda Ayu Melvi Amalia; Armadi Chairunnas; Andhika Puspito Nugroho (Jurnal Biolokus, 2023)
The objective of this study were to identify effective variations in fertilizer doses for phytoremediation of heavy metal nickel (Ni) by using sengon plants (Paraserianthes falcataria) before being used for post-mining land reclamation. This research is an experimental study, the growth parameters measured include plant height, number of leaves, root length, and plant biomass. The data obtained were analyzed using analysis of variance (ANOVA) and continued with Duncan's test. The manure used consists of chicken manure, calcium carbonate, and rice bran. Variation in fertilizer dose is the ratio between manure to mine soil 40:60 (A), 50:50 (B), 60:40 (C), 70:30 (D), and control without fertilizer (E) with four repetitions time. The results showed that there was a significant difference between the concentration of nickel content before and after the treatment of fertilizer dosing (p>0.05), which means that the dose of fertilizer can affect plant growth and phytoremediation abilities. The dose of D fertilizer (70:30) is the most suitable for phytoremediation of heavy metal nickel (Ni) because it shows the highest heavy metal concentration in the roots, which is 3.2 ppm. The plant growth parameters measured showed that the dose of fertilizer B (50:50) was most suitable for increasing plant height and biomass (P. falcataria) with a plant height of 27 cm and a biomass of 0.9 g/m2. The dose of C fertilizer (60:40) is most suitable for increasing the number of leaves with an average of 111.5 leaves. Control without fertilizer (E) is most suitable for increasing the root length of P. falcataria. Thus, the addition of manure affects the growth of P. falcataria, and nickel phytoremediation using P. falcataria at the dose of manure D (70:30) can reduce the nickel content in the soil.